Os temas transversais no ensino-aprendizagem de inglês na escola pública: caminhos para transformações - Silva, André Nascimento da (2018)
This research was developed in a municipal school in the outskirts of Guarulhos, for that to happen, it looked at ten students of a specific multi-series group of Cycle II (EFII) of the modality EJA. It is also understood that this work was developed from the perspective of a case study, in according to what Nunan (1992) explains about this kind of research, it developed from a singular example of a class of objects, in which his investigation occurred in the context in which it occurred, and was also able to provide information on the prevention and resolution of problems related to the workspace in which it developed. The objective of this research was to observe and understand how the relationship between the Transversal Themes and english teaching-learning in the EJA occurs in a critical-reflective perspective of a glocal world. To do so, after raising the profile and the view on Transversal Themes and the english classes in the EJA of ten students who were the participants of this research, a sequence of lessons had been applied to them. What was extracted during these classes was recorded in reflective diaries and recorded in audio by a cell phone and later transcribed, so that one could critically analyse their content, together with the answers of these students, given to a semistructured interview, applied at the end of this sequence of classes. With this research, we sought to observe and understand the possibility of these participants getting used to experiencing continually the critical reflection on the themes that were proposed to them, such as Sexual Orientation, or any others they may one day deal with. In this way, directing this work to a critical paradigm, in which, as clarified by Bredo and Feinberg (1982), it favors the transformation of the individuals involved in a social context of humanity. In order to better understand the content that this research generated, among other theories, these ones were considered: the orientations given by the PCN (1998/2000) about Transversal Themes; Vygotsky's conceptions of teaching-learning (1991/2005), as well as his point of view about cognition and affection, both indispensable, according to the author, to the development of the individual and his vision of the world in the construction of meanings and significance. It was also brought to the light in this work explanations about the term glocal and its importance for the construction of an individual attentive to the world in which it is inserted, according to Celani (2016) and Franco (2003/2008), as well as Freire’s (1982/1999) contributions to Education, based on his concepts on critical pedagogy and other voices such as Rajagopalan (2003) and Moita Lopes (2006). These theories applied to what was built in the classroom together with the students participating in this research, brought the understanding that, through the Transversal Themes, it approached the knowledge in english to their realities, providing them with a significant teaching-learning. While the way the lessons were conducted and the provocations made, even in the mother tongue, they promoted critical reflections about what was studied and awoke some important new glances at students to what is around their glocal universe